Stable isotope ratio analysis of lactose as a possible potential geographical tracer of milk. (September 2022) - Perini, Matteo; Thomas, Freddy; Cabañero Ortiz, Ana Isabel; Simoni, Marco; Camin, Federica
Abstract: With the aim of evaluating the power of the stable isotope ratio analysis of milk lactose as a possible geographic tracer, one hundred and twenty (120) samples of authentic milk from different European countries (Italy, Germany, Austria, France, Spain) were analyzed. The lactose of each was separated and fermented to obtain the alcohol which was analyzed to determine the stable isotope ratios (D/H)I, (D/H)II and δ 13 C. The δ 13 C values showed a close correlation with the diet followed by the animal (C3 and/or C4 plants) while the (D/H)I ratio was more correlated with the δ 18 O of drinking water and therefore with the geographical origin of the milk. Significant differences were found in the (D/H)II ratio of alcohol obtained from the same lactose through the use of different yeasts. The analysis of the δ 18 O of the bulk milk and of the water drunk by the animals showed how the two parameters are closely correlated with each other with differences that can vary according to the type of farm (grazing or not). The method reported here has been validated by two different European laboratories in terms of repeatability and reproducibility. Highlights: The (D/H)I values of ethanol using SNIF-NMR analysis obtained from the fermentation of lactose were analyzed. The proposed method for lactose fermentation was validated in two laboratories. The (D/H)I value gives results similar to measuring the δ 18 O content of milk. The (D/H)I value allows the geographical identification of milk, even in powder form. The use of different bacterial strains did not induce significant isotopic fractionations.